The Influence of Inter-personal Skills on Employee Performance through Teamwork and Employee Work Capabilities : Case Study at the West Papua Regional Secretariat - Febry Jain Andjar; Ahmad Jamil (CV. Creative Tugu Pena, 2024)
Good performance is a goal every organization strives to achieve. This study aims to understand the influence of interpersonal skills on performance through teamwork and employee capability in West Papua. The research was conducted at the West Papua Regional Secretariat, involving 54 employees using a survey method. The unit of analysis in this study is the employees. The analysis method used includes descriptive statistical analysis and SEM (Structural Equation Modeling) with SmartPLS as the analysis tool. The results indicate that teamwork directly contributes the most to the performance of employees at the West Papua Regional Secretariat, with key factors being the balance of team contributions and cohesion within the organization. The role and function of teamwork as an intervening variable in this study are essential, as strong teamwork drives improvements in employee performance at the West Papua Regional Secretariat. Nonetheless, while interpersonal skills and work capability also contribute to performance, work capability has an insignificant effect on employee performance both directly and indirectly.